Semiconductor industrial hygiene handbook : monitoring, ventilation, equipment, and ergonomics - Williams, Michael E., 1949- (Materials science and process technology series., 1995)
This book provides a review of the primary industrial hygiene topics relevant to semiconductor processing: chemical and physical agents, and ventilation systems. Chapters include industrial hygiene concerns that are not specific to the semiconductor industry: ergonomics, indoor air quality, personal protective equipment, plan review, and records retention. While much of the information in these chapters can be applied to all industries, the focus and orientation is specific to issues in the semiconductor industry.